A Dynamic Study with Side Channel against an Identification Based Encryption - Aouinatou, Rkia; Belkasmi, Mostafa; Askali, Mohamed (International journal of communication networks and information security, 2015)
Recently, the side channel keeps the attention of researchers in theory of pairing, since, several studies have been done in this subject and all they have the aim in order to attack the cryptosystems of Identification Based Encryption (IBE) which are integrated into Smart Cards (more than 80% of those cryptosystems are based on a pairing). The great success and the remarkable development of the cryptography IBE in the recent years and the direct connection of this success to the ability of resistance against any kind of attack, especially the DPA (Differential Power Analysis) and DFA (Differential Fault Analysis) attacks, leave us to browse saying all the studies of the DPA and DFA attacks applied to a pairing and we have observed that they have no great effect to attack the cryptosystems of IBE. That is what we will see in this paper. In this work we will illuminate the effect of the DPA attack on a cryptosystems of IBE and we would see on what level we can arrive. Thus in the case where this attack can influence on those cryptosystems, we can present an appropriate counter-measures to resist such attack. In the other part, we will also propose a convenient counter-measure to defend against the DFA attack when the embedding degree is even.